Multispiral Computed Tomography in the Assessment of the Timing of Acute Traumatic Intracranial Hematoma - A. V. Semenov; V. V. Krylov; V. A. Sorokovikov; O. P. Galeeva (Acta Biomedica Scientifica, 2021)
Background. Exact notion about the timing of acute traumatic intracranial hematomas (ATIH) generation is very important to gain a better understanding of the primary and secondary traumatic brain injury (TBI) pathophysiology. The variety of TBI and individual anatomical features of the victims determine the complexity of the issue, as well as the relevance of studies that bring it closer to its solution.Aim of the study was to assess the possibility of using multispiral computed tomography (MSCT) to determine the average timing of the formation of epidural and subdural ATIH.Materials and methods. It is a retrospective study of 84 MSCT investigations of 55 patients with ATIH (epidural – 15, subdural – 40) in Irkutsk City Clinical Hospital N 3 (2018–2019). The ATIH volume calculated by the MSCT. The correlation of ATIH volumes with the period of trauma was studied, as well as a comparison  of average volumes of ATIH among patients distributed in groups in line with the hour of primary MSCT after injury. The dynamics of ATIH of small volumes (up to 40 ml) were assessed in 21 patients left under observation.Results. The volume of epidural ATIH and the time of their detection had no a direct correlation in the period 1 to 4 hours after the injury (p = 0.05). There was no reliable difference in their average volumes per hour of diagnosis, amounting to a total of 54.1 ± 19.7 ml. A direct correlation between the volume of subdural ATIH and the duration of trauma was identified during periods of 1–2 hours (p = 0.02) and 1–3 hours (p = 0.002; t = 3.77) after injury; a true difference in their average volume of 1 and 2 hours after the injury (52 ± 20.2 ml and 106.4 ± 14 ml, respectively). Increase in small ATIH found in 14.3 % of patients left under observation.Conclusions. The MSCT allows us to estimate the average timing of the formation of the main volume of ATIH when hospitalized victims with TBI. The average rate of accumulation of ATIH is about 50 ml per hour, and the direct correlation of their volume and time of diagnosis is reliable the first 2–3 hours after the injury  for subdural ATIH only.